Everything you need to know about organic foods - Dunn-Georgiou, Elisha (New York : The Rosen, 2002)
Discusses the organic food movement and recent information about the United States Department of Agriculture's criteria for what defines an organic food.
Includes bibliographical references and index.
Keywords: Natural foods -- Juvenile literature; Organic gardening -- Juvenile literature